Periphyton Responses to non-point Pollution in Eutrophic-Humic Environments: An Experimental Study - Vilches, Carolina (2014)
We proposed to use artificial channels in laboratory assays to expose periphyton to substances released in rural environments in order to test the following hypotheses 1) a high concentration of humic substances decreases the biofilm biomass and alters its metabolism; 2) periphyton biomass and metabolism increase in response to nutrient addition in spite of the previous high nutrient concentration; 3) periphyton response to nutrient addition is smaller in the presence of humic acids. Nutrient loading associated with nonpoint pollution often occurs both during and after signiûcant precipitation events. Humic acids also increase their levels after rain. This may limit the availability of light and thus, the development of the autotrophic. However, the influence of these pollutants on periphyton in eutrophic environments may be either modest or too difficult to detect using traditional endpoints. We found that in short exposures: 1) humic substances do not decrease the biomass of periphyton nor alter its metabolism; 2) periphyton biomass and metabolism increase in response to the addition of fertilizer but not to the addition of a single nutrient; 3) periphyton response to nutrient addition is smaller in the presence of humic acids. These finding have implications for river ecosystems as they suggest that changes produced by nutrient inputs into the eutrophic stream could be fast and clearly affect periphyton algae and other related organisms such as grazers and decomposers. In addition, the presence of humic acids decreases these responses.